Young people’s participation in the recruitment and selection process for secure care staff - Kirsten McManus (Scottish Journal of Residential Child Care)
The participation of children and young people in decision-making has been an important principle since the ratification of the United Nations Convention on the Rights of the Child (United Nations, 1992). In particular, Article Twelve of the UNCRC upholds the child’s right to be heard. Children and young people can play a valuable role in the recruitment of staff and some agencies are involving them in a purposeful way. By involving children and young people in recruitment, a very clear message can be transmitted about their value and their centrality to the process. Important policy documents have called for greater involvement of children and young people in selection (e.g. Kent, 1997). Research also recognises the political, legal, social and moral reasons for promoting greater participation by young people in matters which affect their lives (Sinclair, 2004). As the main advocacy agency for children and young people in care in Scotland, Who Cares? Scotland has become increasingly involved in the preparation and support of young people in the important task of staff recruitment. This paper outlines the process used by one agency and discusses the difficulties and the